THE EFFECT OF PRODUCT QUALITY, WORD OF MOUTH, AND BRAND TRUST ON PURCHASING DECISIONS OF YUSUF TEMPE MSMES - Rangga Nur Zaifatl Amri; Satrio Sudarso; Lilik Indayani (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research is motivated by the importance of product quality, word of mouth, and brand trust in influencing purchasing decisions in local food MSMEs. The main problem lies in how these three factors contribute to consumers' decisions in choosing Tempe Yusuf products. The purpose of this study is to quantitatively analyze the influence of product quality, word of mouth, and brand trust on consumer purchase decisions. Method: This study uses a quantitative approach with a survey method through the distribution of questionnaires to 96 respondents who have purchased Tempe Yusuf products, selected by purposive sampling technique. 96 respondents were selected because the number met the regression statistical requirements and was considered sufficient to represent the profile of Tempe Yusuf consumers that were relevant to the purpose of the study. Data were analyzed using multiple linear regression with the help of SPSS software. Result: The results showed that product quality and word of mouth had a positive and significant effect on purchase decisions, while brand trust did not have a significant influence. Novelty: The novelty of this study lies in its focus on local food MSMEs, specifically Tempe Yusuf, and its findings emphasize the dominant role of product quality and word of mouth over brand trust in influencing purchasing decisions within the context of local market competition.